SSU rRNA reveals major trends in oomycete evolution - Lara, Enrique; Belbahri, Lassaâd (My University, 2011)
Oomycetes are a group of heterokonts that have a huge impact on the environment as well as on human welfare, due the parasitic nature of many species. However, their evolutionary patterns are still not well understood, due in part to the lack of molecular markers suited to resolve the deep phylogeny of this group. Here, we propose a phylogeny of the whole clade based on the nuclear ribosomal small subunit gene, that comprises both culture and environmental studies derived sequences. Our analysis shows notably that i) plant pathogenesis occurred only rarely in oomycete evolution in comparison to animal parasitism ii) obligate symbiosis happened only in a few derived groups and iii) transitions from soil/freshwater to marine environment (and viceversa) are common unlike for most eukaryotic groups. This study illustrates the complexity of evolutionary patterns and will help to better understand the emergence of pathogenicity in the different oomycete groups.
Keywords: Oomycetes; Pythium; Phytophthora; Albugo; Phylogeny; Plantdiseases; Evolution